The first record of Trichomanes s.s. (Hymenophyllaceae) in Asia and establishment of the new subgenus Asiatrichomanes - Boucheron-Dubuisson, Elodie; Zhao, Yanan; Rouhan, Germinal; Ebihara, Atsushi; Iwatsuki, Kunio; Darnaedi, Dedy; Dubuisson, Jean-Yves (Phytotaxa, 2024)
Callistopteris superba is a peculiar Asian species within the genus Callistopteris (Hymenophyllaceae). A detailed morphological study of available herbarium specimens was conducted and the species was integrated into a global molecular phylogeny of the family in order to more precisely investigate its taxonomy. Morphological analysis and dated phylogenetic reconstructions demonstrate that the species is not part of Callistopteris and is instead strongly supported as being included in the distinct genus Trichomanes, comprising mainly Neotropical and some Afro-Malagasy species. The uniqueness, within the Hymenophyllaceae and the genus Trichomanes, of an indumentum of glandular-like hairs on the adaxial side of the lamina and on the indusia, allows us to propose Asiatrichomanes as a new subgenus based on this species, which is here also neotypified.